Effect of ascorbic acid on Mycobacterium tuberculosis biofilms - Dalton, James P; Uy, Benedict; Swift, Simon; Wiles, Siouxsie (PeerJ PrePrints, 2014)
Planktonic cultures of Mycobacterium tuberculosis, the bacterium responsible for the lung disease tuberculosis (TB), are highly susceptible to killing by ascorbic acid (vitamin C). As planktonically grown M. tuberculosis are unlikely to be representative of the bacterium during infection, we set out to determine if ascorbic acid was also antibacterial against M. tuberculosis growing as a biofilm. We use biofilm growth as a model for the multiple phenotypic states M. tuberculosis can exist in during an infection. In our experiments we employed bioluminescent M. tuberculosis H37Rv (BSGTB1) in which light production is a non-destructive surrogate measure of bacterial viability. Light levels were monitored before and after treatment with 1mM to 256mM ascorbic acid. After 3 weeks of treatment, biofilms were disrupted, washed and inoculated into fresh media to look for sterilisation. Our findings show that ascorbic acid concentrations of 32mM or greater reduced bioluminescence produced by M. tuberculosis BSGTB1 growing in biofilms to background levels and resulted in the death of all cells within the biofilm. This indicates that M. tuberculosis biofilms are susceptible to inhibition and killing by ascorbic acid (vitamin C) and suggests that novel antibiotics with a mode of action similar to ascorbic acid could represent a useful avenue of investigation for TB treatment.
Keywords: Mycobacterium tuberculosis; MTB; TB; biofilm; pellicle; ascorbic acid; vitamin C; antibiotic discovery